Caracterização de propriedades da cera de carnaúba para aplicação na faixa de frequência micro-ondas como substrato de antenas de microfita - Cavalcante, Carlos Eduardo Chaves (Universidade Federal Rural do Semi-Árido, 2019)
Due to greatest technological advancements, the study for the development of new materials for various applications set off an area of great interest, mainly in relation to raw material limitations. For the technology area, the study of new materials for various applications, whether through doping or composite blends, is one of the most important aspects. And, believing in the abundance of carnauba wax from a palmacea species, carnauba, which, for being prominent in the Northeast region of Brazil, and having social, economic and cultural relevance in the semi-arid Northeastern scenario, this work approaches the application of carnauba wax as substrate of microstrip antennas. The electrical characterization of this wax was carried out, as well as the chemical and mechanical characterization. The sample was produced from the heating of the solid carnauba wax (product from the beneficiation of the leaves) through a magnetic stirrer, in which a solid cylindrical structure was acquired to carry out the characterizations of the material. Therefore, the characterizations will serve as the basis of analysis for applications of the organic material in devices that operate in the frequency band microwave, to which the microstrip antennas work. The electrical characterization was performed using the coaxial probe transmission / reflection method. The mechanical characterizations were held to observe the material when submitted to diametrical compression efforts through the digital image correlation and the method used to quantify the microhardness was the Vickers technique. These characterizations will concede obtaining sufficient values for the proposed objective. The antennas were scaled through the models of cavity and transmission line in a program developed in the Fortran language from the relative permittivity and tangent losses. The design and simulation were done in the HFSS® (High Frequency Structural Simulator) to obtain the radiation diagrams (2D and 3D), loss of return and gain. The simulated results were implemented to construct antennas with substrate height of 3 mm to resonate at the 2.45 GHz frequency. Subsequently, the antenna test was done to validate the design data, which represented a good agreement with the simulated results, observed through the reflection coefficient diagram and the Smith chart
Keywords: Substrato dielétrico; Cera de carnaúba; Permissividade elétrica; Tangente de perdas; Material orgânico; Dielectric substrate; Carnauba wax; Electrical permissiveness; Tangent of losses; Organic material; ENGENHARIAS::ENGENHARIA ELETRICA